2012
DOI: 10.1051/ata/2012011
|View full text |Cite
|
Sign up to set email alerts
|

A simple toxicological analysis of anabolic steroid preparations from the black market

Abstract: -Objectives:A simple and rapid gas chromatography (GC) method with mass spectrometry (MS) detection was developed for the identification and quantification of anabolic steroids in pharmaceutical preparations from the black market. Material and Methods: After a liquid-liquid extraction of pharmaceutical products at acidic, neutral and basic pH with chloroform-isopropanol (9:1, v/v), the different steroids were separated by fused silica capillary column and detected by electron impact (EI)-MS in positive ionizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
13
0
3
Order By: Relevance
“…Despite few doubting the reliability of the steroids accessed, the forensic analysis of the 10 samples sourced revealed that only three actually contained what was stated on the packaging and those that did had very low active ingredients compared with the strength indicated (see Coomber et al 2014 for further discussion on this). This is in line with international studies which highlight the variation in the forensic composition of steroids (Coopman and Cordonnier, 2012;Graham et al, 2009;Kohler et al, 2010;Pellegrini et al, 2012;Thevis et al, 2008). Coomber et al (2014, p. 138) point out, however, that caution is needed in extrapolating health risks from such data: 'inauthentic substances will present different risks and many of these will not be necessarily high risk nor the product of cynical acts'.…”
Section: Quality Controlsupporting
confidence: 62%
“…Despite few doubting the reliability of the steroids accessed, the forensic analysis of the 10 samples sourced revealed that only three actually contained what was stated on the packaging and those that did had very low active ingredients compared with the strength indicated (see Coomber et al 2014 for further discussion on this). This is in line with international studies which highlight the variation in the forensic composition of steroids (Coopman and Cordonnier, 2012;Graham et al, 2009;Kohler et al, 2010;Pellegrini et al, 2012;Thevis et al, 2008). Coomber et al (2014, p. 138) point out, however, that caution is needed in extrapolating health risks from such data: 'inauthentic substances will present different risks and many of these will not be necessarily high risk nor the product of cynical acts'.…”
Section: Quality Controlsupporting
confidence: 62%
“…More recently, Graham et al [38] A further study from Germany [40] yielded similar results with only four of 11 confiscated black market products containing the substance and amount declared on the label. Showing consistency across borders a recent Italian study [41] found that only two of 15 pharmaceutical preparations seized by authorities contained the content stated on the labels. In each of the other cases, either no PIED were present at all or steroids different from those listed on the labels or different amounts from those declared were found.…”
Section: The Forensic Evidencementioning
confidence: 99%
“…The literature describes several methods for determination of the authenticity and quantification of anabolic steroids in different pharmaceutical formulations, highlighting chromatographic methods including gas chromatography [7,8,11,12] and liquid chromatography [9,[13][14][15]. However, although these techniques are well established for this type of analysis, with good detection limits, they have a number of disadvantages from the operational point of view, such as the need for specific chromatographic columns, laborious sample preparation steps, and sometimes the use of derivatization reactions and toxic solvents.…”
Section: Introductionmentioning
confidence: 99%